2009
DOI: 10.1080/09709274.2009.11906153
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Pattern and Nutritional Status of Women in Orissa: A Rural-Urban Differential

Abstract: As per the estimates of National Family Health Survey, Orissa lies far behind the national average in terms of many important aspects of nutrition. The problem is definitely more acute in case of the women staying in rural areas. This paper tries to find out the variation in food consumption and nutritional status of women in the state in rural and urban areas against different background variables. It also attempts to capture the difference between standard and actual level of food intake among different grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…They give emphasis on consumption of cereals only. The present study is in accordance with Rout (2009) who reported that in Orissa state almost half of the rural women (48.60 %) were underweight and 3.30 percent were low weight.…”
Section: Resultssupporting
confidence: 93%
“…They give emphasis on consumption of cereals only. The present study is in accordance with Rout (2009) who reported that in Orissa state almost half of the rural women (48.60 %) were underweight and 3.30 percent were low weight.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, it was found that 1/3 rd of the women's are underweight, a similar study conducted Lagos state of Africa found the same findings [14]. A similar study conducted by the National Institute of Nutrition found the same findings [15].…”
Section: Discussionsupporting
confidence: 79%
“…However, religiously, even diverse food preparation practices with rituals have little effect on nutrition. [12][13][14] Economic, health, medicine, food, and so on compared to the rural area, so in most urban areas, people consume more food due to greater economic strength and purchasing power parity compared to the rural area, which impacts nutrition. Wealth is an essential factor in nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, some paradoxes also found that those who wanted to lose weight reported lower food intake than those with a lower BMI. 12 Marital status, equality and family size are the most interrelated population characteristics. If a married woman belongs to a large family in India, women eat almost all family members after meals, consuming the rest of the food, resulting in malnutrition among them.…”
Section: Discussionmentioning
confidence: 99%